Sustainability and Financial Outcomes: The Impact of ROA, ESG, and Firm Size on Tax Avoidance - Anis Lestari; Anggita Shita Kusumawati; Aprildawati Sinaga; Izdihar Shada; Rolas Tarida Sianturi (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to examine the effect of Return on Assets (ROA), Environmental, Social, and Governance (ESG), and firm size on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. This research employs a quantitative approach using secondary data obtained from corporate financial statements and sustainability reports. The sample was selected through purposive sampling, resulting in 216 observations. Multiple linear regression analysis was conducted using Stata software, accompanied by classical assumption tests and hypothesis testing. The results indicate that ROA and ESG have a significant negative effect on tax avoidance, suggesting that firms with higher profitability and stronger sustainability performance tend to exhibit higher tax compliance. Meanwhile, firm size shows a significant positive effect on tax avoidance. Simultaneously, ROA, ESG, and firm size significantly influence tax avoidance. These findings support Legitimacy Theory and provide implications for corporate management and policymakers in promoting corporate tax compliance.